Reduced Balance Restoration Capacities Following Unilateral Vestibular Insult in Elderly Mice - Cassel, Raphaelle; Wiener-Vacher, Sylvette; El Ahmadi, A.; Tighilet, Brahim; Chabbert, Christian (Frontiers in Neurology, 2018)
Acute vestibular syndrome (AVS) is characterized by severe posturo-locomotor and vestibulo-oculomotor impairment and accompanies several types of peripheral vestibulopathies (PVP). We know very little about its aetiology, how its various symptoms are expressed and how it evolves with age. Robust repair capabilities of primary vestibular synapses have recently been shown to restore behavioral functionality. In this study, we used a mouse model of an excitotoxically induced unilateral vestibular lesion to compare the ability to restore balance and posture between old and young adult mice. We compared the temporal evolution of the evoked vestibular syndrome using a battery of behavioural tests to follow the evolution of postural-locomotor alterations and equilibrium. For the first time, we show that young adult (3 months) and elderly (22 months) mice are together able to restore normal postural-locomotor function following transient unilateral excitotoxic vestibular insult, though with different time courses. This animal study paves way for future, more detailed studies of how the early postural and locomotor disturbances following a unilateral insult are compensated for by various plasticity mechanisms, and in particular how age influences these mechanisms.